QUALITY OF LIFE AND TREATMENT ADHERENCE AMONG POSTMENOPAUSAL WOMEN WITH OSTEOPOROSIS AT DUC GIANG GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe quality of life and treatment adherence among postmenopausal women with osteoporosis receiving outpatient treatment at Duc Giang General Hospital.Subjects and methods: A cross-sectional descriptive study was conducted on 220 postmenopausal women with osteoporosis receiving outpatient treatment at Duc Giang General Hospital from August to December 2025. Osteoporosis was diagnosed according to World Health Organization standards. Quality of life was assessed using the SF-36 scale and treatment adherence was assessed using the GMAS scale.Results: The overall quality of life score was 53.8 ± 11.6; physical quality of life score was 51.2 ± 13.1; mental quality of life score was 56.6 ± 12.4; 54.5% of patients had an average quality of life; 39.1% had a low quality of life. 55.5% of patients did not adhere to treatment, with an average GMAS score of 25.8 ± 4.6. The group with good treatment adherence had higher quality of life scores compared to the group with poor adherence (60.2 ± 9.8 vs. 48.8 ± 10.4; p < 0.001).Conclusion: The quality of life of postmenopausal women with osteoporosis receiving outpatient treatment is moderate and is correlated with treatment adherence. Increased counseling and improved treatment adherence are needed to enhance patients’ quality of life.
Keywords: Osteoporosis, quality of life, medication adherence.